2021
DOI: 10.1038/s41598-020-79982-9
|View full text |Cite
|
Sign up to set email alerts
|

Natural sonic crystal absorber constituted of seagrass (Posidonia Oceanica) fibrous spheres

Abstract: We present a 3-dimensional fully natural sonic crystal composed of spherical aggregates of fibers (called Aegagropilae) resulting from the decomposition of Posidonia Oceanica. The fiber network is first acoustically characterized, providing insights on this natural fiber entanglement due to turbulent flow. The Aegagropilae are then arranged on a principal cubic lattice. The band diagram and topology of this structure are analyzed, notably via Argand representation of its scattering elements. This fully natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Moreover, aegagropiles from Posidonia oceanica, the spherical aggregates formed by fibers from this phanerogam, show a high sound absorption capacity [55]. This characteristic might be present in living vegetation, which would also explain the current results.…”
Section: Acoustic Detection and Characterization Of P Oceanica Meadowssupporting
confidence: 68%
“…Moreover, aegagropiles from Posidonia oceanica, the spherical aggregates formed by fibers from this phanerogam, show a high sound absorption capacity [55]. This characteristic might be present in living vegetation, which would also explain the current results.…”
Section: Acoustic Detection and Characterization Of P Oceanica Meadowssupporting
confidence: 68%
“…Perfect absorption in a duct propagation problem can be obtained when the propagation symmetry is broken [3], when degenerated resonators are used [9], or when symmetry inversion frequency is tuned [19]. The simplest system is thus an asymmetric absorber [3] that is composed of at least two different resonators placed at a finite distance from each other along the duct axial direction.…”
Section: Asymmetric Absorber Lining a Duct Of Constant Cross Sectionmentioning
confidence: 99%
“…They have also been shown to be a suitable source of lignocellulosic fibres to produce pulp and paper [26]. In addition, a crystal absorber constituted of Posidonia oceanica fibrous spheres can be made to develop acoustic materials [27]. Recently, a study on the benefits of Posidonia oceanica leaf extracts to treat diseases revealed anti-inflammatory properties [28] and the inhibition of human cancer cell migration [29].…”
Section: Introductionmentioning
confidence: 99%